A formação de leitores de fotografias como prática integrativa de promoção de saúde na oncologia - Barelli, Cristiane (2019)
The postmodern society daily challenges health teams to re-signify their practices and promote comprehensive care that reaches the depth of their ways of being and ways of life, especially in the area of Oncology. Technological and scientific advances, despite qualifying diagnoses and therapies, may compromise the focus of the relationship between professionals and the subject of care. Because cancer is an aggressive disease and causes profound impacts to the patient, the emerging image of psychic life unites and centralizes the facts, as if it were a photograph of the moment the person experiences it. Understanding this "photograph" can open up possibilities for self-knowledge, understanding and acceptance of the disease. This research deals with the training of photographic image readers as a strategy of health promotion and humanized care in Oncology. It sought to verify if, through the training of image readers, it would be possible to trigger subsidies for the qualification of health care in people who experience cancer. The objective was to investigate the meaning attributed by the people involved with cancer care to the images produced by them and what these subjects revealed from the perspective of humanized care and integrative health practices, in the light of Gilbert Durand's theory of the imaginary. This is a qualitative, descriptive-interpretive study of a symbolic hermeneutic approach, supported by Gilbert Durand's Imaginary Theory, approved by the Research Ethics Committee of the University of Passo Fundo. The path taken, in addition to the initial phases, consists of two training workshops for photo readers: one for medical and nursing students; another one for professionals linked to the Integrated Multiprofessional Residency Program in Cancer Care at the São Vicente de Paulo Hospital. They were developed with active methodologies, in five meetings of 90 minutes each. Participants who were attending the five meetings included the study sample, totaling five students and seven residents. The data collection used a tab of the participants' profile, an open interview and the researcher's field diary. To understand the results, we considered the productions of the last meeting, read by the Singular Individual Transtextual Reading method proposed by Ormezzano. From the iconic text elaborated by the participants, we look for the references of the imaginary in the light of the Durandian theory by the identification of the schéme, archetype and symbolic motivations, considering the dynamism and the convergence of the symbols in the isomorphic structures. The results were organized into three strands: the importance of image in health education, humanized care and the perspective of different perspectives. The meaning attributed by students and professionals to the process of training photographic image readers in the perspective of humanized cancer care and integrative health practices enlighted by Imaginary